Radiation dose management of pregnant patients, pregnant staff and paediatric patients diagnostic and interventional radiology (IOP ebooks, 2020)
Whenever a diagnostic or interventional X-ray examination of a pregnant patient is considered to be necessary, conceptus dose estimation is an essential step in assessing the radiogenic risks to the unborn child. Accurate estimation of embryo/fetus radiation dose is also needed after accidental exposure of a pregnant patient from an X-ray procedure. The exposure of pregnant patients to medical X-rays is often a complex case and involves emotionally sensitive issues for both prospective parents and physicians. Conceptus dose assessment is not always easy. Medical physicists should be able to assess conceptus doses and risks from diagnostic and interventional procedures and also to place the risk in a perspective from which an informed decision can be made. Pregnant medical professionals working with radiation have many misconceptions about the risks of ionizing radiation on the unborn child. Medical radiation workers of childbearing age should be aware that careful planning and dose optimization of examinations can address their concerns and permit, in the vast majority of cases, safe performance of procedures. Pediatric patients requiring diagnostic and interventional procedures are exposed to diagnostic and interventional X-rays. Pediatric patients are more sensitive to radiation than adults and, for this reason, accurate assessment of doses and risks is needed in these cases. Medical physicists should be able to assess paediatric doses and risks from diagnostic and interventional procedures. Several techniques and tools have been developed for dose optimization of radiographic, fluoroscopic, computed tomography and fluoroscopically-guided interventional pediatric procedures. The scan parameters should be adjusted for patient size and body region. Part of Series in Physics and Engineering in Medicine and Biology